Familiealbum : Vlaamse auteurs schrijven over hun voorouders - Kuypers, Julien; Mussche, Achilles; Van Aken, Piet; Lampo, Hubert; Gijsen, Marnix; Teirlinck, Herman (Antwerpen : Ontwikkeling, 1955)
Bibliotheek Camille Huysmans
Nederlands
Monografie